Causal Effects of Genetically Predicted Cystatin C on Osteoporosis: A Two-Sample Mendelian Randomization Study - Yuan, Jiaqin; Peng, Lipeng; Luan, Fujun; Li, Jie; Zhang, Jinglin; Jiang, Wei; Wang, Wenting (Frontiers in Genetics, 2022)
Objectives: Although it has long been reported that high levels of cystatin C could contribute to the development of osteoporosis in some studies, no evidence has established a causal association between them thus far. Methods: A Mendelian Randomizationrandomization (MR) study was conducted to determine the causal effect of cystatin C on osteoporosis based on public databases obtained from separately published genome-wide association study (GWASstudies (GWASs). The single- nucleotide polymorphisms (SNPs) for cystatin C were extracted from the MR-Base (CKDGen, 33,152 participants), and the SNPs for osteoporosis were extracted from the UK Biobank project (UK Biobank, including 5,266 osteoporosis cases and 331,893 controlcontrols). We defined the odds ratio (OR) of IVW methods as the primary outcome. BesidesIn addition, weighted median and MR–EggerMR -Egger regressions were used in the sensitivity analysis. Results: In IVW, we found that the genetically predicted cystatin C was causally associated with the risk of osteoporosis with an OR of 1.02 [95% ﻿confidence interval (CI) = 1.003-1.025, P = 0.01]. In the further sensitivity analysis, weighted median regression also showed directionally similar estimates (OR = 1.02, 95% CI = 1.005-1.03, P = 0.005]005), and MR–EggerMR-Egger regression (OR = 1.02, 95% CI = 1.000-1.036, P = 0.15) revealed similar estimates but with lower precision. The funnel plot, MR–EggerMR-Egger intercept, and MR-PRESSO all indicate that no directional pleiotropic effect was observed. Conclusions: In conclusion, our MR study showed evidence of a causal association between serum cystatin C levels and osteoporosis, and itwhich also needs to be verified by studies with larger sample sizes in the future. Early monitoring of cystatin C may enable us to prevent osteoporosis-related diseases.